The Subkoss Garuda Sriwijaya Struggle Museum in the Efforts to Preserve Local History in Lubuklinggau - Ravico; Berlian Susetyo; Sisca Arie Hanika; Muhammad Natarsyah (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2025)
The Garuda Sriwijaya Subkoss Struggle Museum is a museum unit managed by the South Sumatra State Museum Technical Implementation Unit, South Sumatra Provincial Culture and Tourism Office. This museum is categorised as a special museum that displays the struggle of the physical revolution to defend the independence of the Republic of Indonesia in South Sumatra in 1945-1949. In addition to being a source of learning, the museum acts as preserving objects of historical and cultural value through programmes implemented by the museum itself and making the museum a local history education by bringing in visitors. This research discusses in detail the history and policies of the museum in preserving local history in Lubuklinggau. This research uses narrative qualitative research. The results of the research obtained that the Garuda Sriwijaya Subkoss Struggle Museum is a museum that has a large collection of objects of the struggle of the people in Lubuklinggau and its surroundings in an effort to maintain independence, so that in 1988 it was inaugurated as a museum. After the museum collection has been classified according to category, then make a museum exhibition policy to support the introduction and preservation of local history in Lubuklinggau.